2020
DOI: 10.3390/rs12162650
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Influence Elimination and Chlorophyll Content Diagnosis of Maize Using UAV Spectral Imagery

Abstract: In order to improve the diagnosis accuracy of chlorophyll content in maize canopy, the remote sensing image of maize canopy with multiple growth stages was acquired by using an unmanned aerial vehicle (UAV) equipped with a spectral camera. The dynamic influencing factors of the canopy multispectral images of maize were removed by using different image segmentation methods. The chlorophyll content of maize in the field was diagnosed. The crop canopy spectral reflectance, coverage, and texture information are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Various types of sensors mounted on UAV platforms, such as multispectral, hyperspectral, RGB, and thermal, are being widely used in the phenotypic evaluation of crops, with satisfactory data accuracy. The UAV-based nondestructive multispectral assessments of the LAI ( Comba et al, 2020 ), biomass ( Yue et al, 2019 ), chlorophyll content ( Qiao et al, 2020 ), nitrogen use efficiency ( Yang et al, 2020 ), senescence ( Hassan et al, 2021 ), and GY ( Hassan et al, 2019a ) have been reported for several crops. These assessments are based on the spectral reflectance from the canopy of plants in the form of light bands with different wavelengths ( Li et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various types of sensors mounted on UAV platforms, such as multispectral, hyperspectral, RGB, and thermal, are being widely used in the phenotypic evaluation of crops, with satisfactory data accuracy. The UAV-based nondestructive multispectral assessments of the LAI ( Comba et al, 2020 ), biomass ( Yue et al, 2019 ), chlorophyll content ( Qiao et al, 2020 ), nitrogen use efficiency ( Yang et al, 2020 ), senescence ( Hassan et al, 2021 ), and GY ( Hassan et al, 2019a ) have been reported for several crops. These assessments are based on the spectral reflectance from the canopy of plants in the form of light bands with different wavelengths ( Li et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Qiao et al (2020) [46] described a segmentation-based method to estimate chlorophyll content at different maize growth stages using multispectral imagery. They showed different segmentation results that produced variations in the extraction of maize canopy parameters, with the wavelet method as the best output.…”
Section: Assessment Of Nitrogen Content/deficienciesmentioning
confidence: 99%
“…To extract specific information from multispectral images, vegetation indexes (VIs) have been proposed, which result from arithmetic combinations of images of different wavelengths. In agriculture, they can highlight vegetation health, photosynthetic activity, and leaves' chlorophyll concentration [22][23][24][25][26][27][28]. The best-known indexes are the Normalized Difference Vegetation Index (NDVI) [29] for chlorophyll content and the Normalized Difference Red-Edge (NDRE) for plant nitrogen diagnosis [30].…”
Section: Introductionmentioning
confidence: 99%